Comparison of the Effect of Apium Graveolens L Decoction and Annona Muricata L Decoction on Blood Pressure Reduction in Pre-Elderly - Andi Bintang; Radiah Ilham (Indonesian Journal of Global Health Research, 2024)
Hypertension is a non-communicable disease and is a major factor in health problems in the world because of its high prevalence. In general, a person is considered to have hypertension if his blood pressure is more than 140/90 mmHg. So hypertension is a big challenge in Indonesia because it is often found in primary health services or in health centers. This study aims to determine the comparison of the Effect of Apium Graveolens L Decoction and Annona Muricata L Decoction on Reducing Blood Pressure in the Pre-Elderly at the Bajoe Health Center, Bone Regency. This study is a quasi-experimental study with a non-equivalent pretest-postest design with control group. The sample in this study is Pre-Elderly aged 45-59 years with a diagnosis of hypertension as many as 40 people at the Bajoe Health Center, Bone Regency. divided into two groups, namely the Apium Graveolens L decoction intervention group of 20 people and the Annona Muricata L decoction intervention group of 20 people according to the inclusion and exclusion criteria. Based on the dependent t-test statistical test, it can be seen that there is an effect of Apium Graveolens L decoction on the decrease in blood pressure with a p- value of 0.000 (p<0.05), while the results of the dependent t-test statistical test can be seen that there is an effect on the decrease in systolic blood pressure with a value of p 0.000 (p<0.05). Meanwhile, diastolic blood pressure has no effect with a value of p 0.106 (p>0.05). So it can be concluded that there is a comparison of the effect of Apium Graveolens L decoction and Annona Muricata L decoction on the reduction of blood pressure in the pre-elderly.